Influence of physical activity on linear growth in children and adolescents - Jazbinšek, Sončka; Kotnik, Primož (Annales Kinesiologiae, 2020)
Linear growth is the result of bone elongation in children and adolescents mediated by processes of endochondral ossification and maturation of bone tissue. Physical activity (PA) importantly influences both processes through systemic and local effects, mediated by growth hormone, insulin-like factor I, sex hormones, thyroid hormones, glucocorticoid hormones and various cytokines with endo-, para- and autocrine function, secreted by adipose tissue (adipokines) or muscles (myokines). It is important to promote a physically active lifestyle already in early childhood as it tends to persist into adulthood together with favorable body composition. From the safety point-of-view, recent data suggests that PA does not negatively influence linear growth regardless of its duration or intensity, as long as chronic negative energy balance is prevented by sufficient energy intake. The aim of this review is to describe current scientific knowledge on the mechanisms by which PA could influence linear growth and present recent studies analyzing its possible effects.